2020
DOI: 10.1007/s42729-020-00185-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Availability and Physiological Response of Corn After 12 Years with Organic and Mineral Fertilization

Abstract: The study aimed to evaluate the effects of long-term organic and mineral fertilization on soil solution dynamics of nitrogen (N), as well as to understand its relationship with corn plant growth, plant N uptake, and grain yield. The study was conducted in Santa Maria, State of Rio Grande do Sul, Brazil, for 12 years. The treatments consisted of pig slurry (PS); cattle slurry (CS); pig deeplitter (PL); mineral fertilizer (NPK); and no fertilization (control). We determined concentrations of dissolved inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…In agreement with these findings, Martinez et al (2017) and Cavalli et al (2016), who conducted field experiments in Mediterranean countries, found that manure treatments increased corn yield in comparison to the untreated control. Similar results for corn are also reported by Marchezan et al (2020), after cattle slurry application to soil for 12 years. Moreover, Cavalli et al (2016) reported that, after 3 consecutive years of manure (liquid, solid, untreated) application, N uptake by corn and Italian ryegrass (Lolium multiflorum Lam.)…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In agreement with these findings, Martinez et al (2017) and Cavalli et al (2016), who conducted field experiments in Mediterranean countries, found that manure treatments increased corn yield in comparison to the untreated control. Similar results for corn are also reported by Marchezan et al (2020), after cattle slurry application to soil for 12 years. Moreover, Cavalli et al (2016) reported that, after 3 consecutive years of manure (liquid, solid, untreated) application, N uptake by corn and Italian ryegrass (Lolium multiflorum Lam.)…”
Section: Discussionsupporting
confidence: 88%
“…As in the present study, Marchezan et al (2020), who evaluated cattle slurry, pig slurry, and pig deep-litter as organic fertilizers for corn in comparison to inorganic fertilization, after field applications for 12 years, reported ANR values of the same magnitude for cattle slurry and N-P-K fertilization treatments. The respective values for the other two organic amendments were much lower.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The composition and quantity of plant residues left by a crop, alter soil nutrient cycles in complex ways (Urquiaga et al, 1998). For instance, depending on the quality (chemical nature) of the residues and the prevalent environmental conditions, nutrients, such as N, can be either immobilized in soil/residues or mineralized and released into the soil solution, becoming available for plant uptake (Urquiaga et al, 1998;Marchezan et al, 2020). There are also nutrient losses due to volatilization and leaching during the mineralization process, and depending on residue quality, these elements may not be fully released during the next crop cycle, although they may become available in the system in the long term.…”
Section: Decomposition Of Urochloa Residues and Nutrient Releasementioning
confidence: 99%
“…Nitrogen (N) is the most essential nutrient for vegetative plant growth (Marchezan et al, 2020). The nitrogen induces the plant growth and carbohydrate and protein metabolism.…”
mentioning
confidence: 99%